PT Pertamina Patra Niaga DPPU Supadio Pontianak's Corporate Social Responsibility (CSR) Program Initiative as an Effort to Develop Sungai Kupah Tourism Village Through Community Capacity Building in Managing Environmental Resources - Reza Fardiansyah Putra Dinata*; Wily Wicaksono; Wibisono Wibisono; Amrizarois Ismail (Universitas Syiah Kuala, 2023)
PT Pertamina Patra Niaga DPPU Supadio is one of the operating units of Sub Holding Commercial and Trading PT Pertamina (Persero), which is one of the state-owned oil and gas companies in Indonesia. As an operating unit, PT Pertamina Patra Niaga DPPU Supadio is responsible for receiving, stockpiling and distributing aviation fuel at Supadio Pontianak Airport. Based on statistical data from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration (Kemendes PDTT) in 2018, there are 141 tourist villages in West Kalimantan Province, one of which is Sungai Kupah Village which is a priority tourism village in the province. Sungai Kupah Village, which is synonymous with coconut plantations, in fact leaves several problems, apart from the small number of variants of the type of community work, which results in suboptimal economic income, the potential for contaminants from plantation waste in the form of coconut coir that has accumulated over the years, changes in the function of mangrove forest land into coconut plantations. is also a problem that has the potential to cause an environmental disaster for the community. It is on this basis that Pertamina DPPU Supadio's CSR program carries out an initiative program that focuses on environmental aspects, welfare and improving the community's economy. Using a combination of descriptive and quantitative qualitative methods, this study attempts to describe the operation of Pertamina DPPU Supadio's CSR initiative program and its benefits to society and the environment. As a result, it can be described that Pertamina DPPU Supadio's CSR initiative program provides positive benefits including for mangrove conservation, reducing disaster potential, increasing people's welfare and economy through the establishment of Sungai Kupah Tourism Village as a tourism priority village for West Kalimantan Province.